Development of laboratory work module for production of soap based on local resources as the integration of chemistry lessons with workshop and entrepreneurship - Andi Maria Ulfa; Amirul Hilmi; Isna Rezkia Lukman (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The study aims to develop and test the feasibility of a locally developed soap-making module based on local resources. The research method used is research and development (R&D), which is adapted from the Borg & Gall R&D method. There are ten stages of research with three stages of testing/assessment. Stage I assessment by experts (chemistry/chemistry learning, economics/economics learning, language, and graphic design), stage II assessment by peer reviewers/colleagues, and stage III assessment by chemistry teachers and teachers of crafts and entrepreneurship. The assessment results by experts got a total score of 58, which was in the good category. The assessment results by economists/learning economics got a total score of 72, which was in the very good category. The result of the assessment by the linguist got a total score of 57 in the very good category. Finally, the result of the assessment by the graphic design expert got a score of 39 in the good category. The second stage of the assessment by five peer reviewers received an average total score of 69.6 in the good category, while the assessment results by the chemistry teacher and PKwu were 72.6 and 74 in the very good category, respectively. The overall assessment results show that the module is in the good and very good categories; therefore, the module is feasible to be developed and used further. While the results of the assessment by the chemistry teacher and PKwu, respectively, were 72.6 and 74, with a very good category. The overall assessment results show that the module is in the good and very good categories, so it can be concluded that the module is feasible to be developed and used further.